The importance of microscopic diagnosis of respiratory infections - Isabella Princess; Rohit Vadala (Apollo Medicine)
The need for mastering microscopic diagnosis arises in all laboratory specialties, especially when working in resource-poor community laboratories which lack newer diagnostic instruments. Certain clues from microscopic appearance should be carefully analyzed to clinch diagnosis and to not miss out these findings. In addition, if turnaround time is reduced, there is better patient outcome and satisfaction from the clinical colleagues.